Cow's milk allergens: Screening gene markers for the detection of milk ingredients in complex meat products. (February 2020) - Villa, Caterina; Costa, Joana; Oliveira, M. Beatriz P.P.; Mafra, Isabel
Abstract: Cow's milk proteins are food allergens present in uncounted foodstuffs. By exploiting and comparing different regions of bovine genome, this work intended to develop a real-time PCR method to detect/quantify traces of milk in complex foods. Two mitochondrial ( cytb and 12S rRNA) and two nuclear (β-lactoglobulin and β-casein) genes showed the most promising results by qualitative PCR. However, real-time PCR assays targeting nuclear genes revealed cross-reactivity with some meat species, while the 12S rRNA assay was the most specific (only minor reactivity with two species above 36 cycles of amplification), providing a linear dynamic range of 10–0.05% of cow's milk protein concentrate (MPC) in raw meat and cooked ham, with acceptable performance parameters. The results highlight the potentiality of the assay for the development of a novel method to quantify milk ingredients in meat products. Highlights: Several mitochondrial and allergen-encoding genes were evaluated for cow detection. Cytb, 12S rRNA, β-lactoglobulin and β-casein genes were the most promising. Real-time PCR revealed cross-reactivity with other meat species. Real-time PCR targeting the 12S rRNA gene with a TaqMan probe was the most specific. It provided linearity within 10–0.05% of cow's milk protein concentrate in mixtures.